Aspectos socioculturales y técnico-nutricionales en la alimentación de un grupo de adultos mayores del Centro Gerontológico Colonia de Belencito de Medellín-Colombia (2010)
ABSTRACT: The main purpose of this research was to determine social and cultural characteristics influencing alimentary and nutritional aspects of elderly people, living in a center care called Colonia de Belencito Medellin. Methods: This is a qualitative study that including different techniques to collect data like direct observational process, semi structured surveys and focus groups method. Results: The main results showed in this study was that elderly concept and sociocultural characteristics influencing nutrition behaviors in this population, don’t fit with the proposed model for an active and healthy elderly process; the specific techniques to design menus for this specific group of population are submitted to a classical medical nutrition model: elderly people affirmed that they prefer traditional food, because of it is a socializing process that establish cultural identity of alimentary meaning.